ANALISIS IMPLEMENTASI PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA DI SD KRISTEN RANTEPAO 5 - Junaidi, Renta; Trivena; Hendrik (Al-mujahidah, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile at SD Kristen Rantepao 5. The research uses a qualitative approach with a descriptive research type. Data were collected through observation, interviews, and documentation. The results show that the implementation of the Pancasila Student Profile at SD Kristen Rantepao 5 is carried out through various activities involving the entire school community. The first dimension, belief and devotion to God, is implemented through prayers and moral values education. The second dimension, global diversity, is reflected in the appreciation of differences through cultural activities and group work. The gotong royong dimension is emphasized in classroom cleaning and collaboration among students. The independent, critical thinking, and creative dimensions are implemented through individual tasks and innovative projects. The study concludes that the implementation of the Pancasila Student Profile at the school is effective, although there are still challenges in its implementation.